Indonesian Lexical Interference into Baduy Sundanese Dialect - Darmawan, Zelline Nur Intanawaty Dalillah; Isnendes, Retty; Hernawan, Hernawan (SCOPE: Journal of English Language Teaching, 2024)
This research was conducted because of the phenomenon of Indonesian language interference in one of the Baduy figures. The purpose of this research is to know and describe the forms of Indonesian lexical interference into Baduy dialect Sundanese, as well as to describe the factors causing the occurrence of Indonesian lexical interference into Baduy dialect Sundanese. The method used in this research is descriptive qualitative method. The data of this research are the basic forms of Indonesian language that enter into Sundanese language in Aka Mursid's interview video. The researcher uses non-participant observation category, which means that the researcher does not take part directly in the activities being observed. The data were analyzed by collecting sentences containing lexical interference using ELAN application. Based on the result of the research, the researcher concludes that there are two factors that cause Indonesian lexical interference into Sundanese language of Baduy dialect, linguistic and non-linguistic. The linguistic factor is due to the almost equal mastery of B1 and B2 of the Baduy community, as well as the factor of bilingualism. The non-linguistic factor is due to the habit and environment of Baduy people who are visited by outsiders and tourists who use Indonesian. This research has a contribution to teachers who teach Sundanese and Indonesian as a comparison of language and cultural habits in Baduy and outside Baduy.